Bayadome Geotours (BATOUR) Prototype for Geosite Management at Bayah Dome Geopark, Banten - Munandar, Tb Ai; Sri Lestari, Tyastuti; Handayani, Dwipa; Noe’man,, Achmad; Fathurrazi, Ahmad; Priatna, Wowon; Karyaningsih, Dentik; Kapriadi, Engkap (Jejaring Penelitian dan Pengabdian Masyarakat, 2024)
The objective of this study is to create a technology-driven application prototype, named